Data science in chemistry : artificial intelligence, big data, chemometrics and quantum computing with Jupyter - Gressling, Thorsten (De Gruyter Textbook, 2020)
The ever-growing wealth of information has led to the emergence of a fourth paradigm of science. This new field of activity - data science - includes computer science, mathematics and a given specialist domain. This book focuses on chemistry, explaining how to use data science for deep insights and take chemical research and engineering to the next level. It covers modern aspects like Big Data, Artificial Intelligence and Quantum computing.